The Middle and Lower Xingu: the response to the crystallization of different temporalities in the production of regional space - Juliana Mota de Siqueira (Revista Brasileira de Estudos Urbanos e Regionais (RBEUR), 2017)
While the region of the Middle and Lower Xingu has been a protagonist during many episodes of Brazilian history, it remains unknown to a large cross-section of society. Within this perspective, we have revealed some of the different elements responsible for the production of regional space by joining theoretical exercise with empirical, which signifies combining some of the knowledge that has been produced on the region with the discourse of some of the different agents involved in its transformation. Accordingly, the following processes were adopted as markers: colonization, the opening of the Trans-Amazonian, land conflicts and the construction of the Belo Monte Hydroelectric Power Plant. As part of this collective effort, based on interviews with the central institutions (from the First, Second and Third sectors), and with communities from different locations within the region, this article gathers together arguments that contribute to the debate regarding the accumulated processes in the Brazilian Amazon, and particularly in the Middle and Lower Xingu.